2018
DOI: 10.31234/osf.io/7j4s2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the transcriptional signatures of hub connectivity in neural networks

Abstract: Connections in nervous systems are disproportionately concentrated on a small subset of neural elements that act as network hubs. Hubs have been found across different of species and scales ranging from C.elegans to mouse, rat, cat, macaque and human, suggesting a role for genetic influences. The recent availability of brain-wide gene expression atlases provides new opportunities for mapping the transcriptional correlates of large-scale network-level phenotypes. Here we review studies that use these atlases to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…These advances have prompted the development of statistical approaches designed to identify genes involved in neuronal connectivity. At coarser spatial scales, where collections of spatially proximal neurons are profiled together, data availability has led to the development of correlative and predictive approaches that connect regional gene expression and connectivity in the mouse brain (25,26). At the neuronal scale, Kaufman et al (27) demonstrated a correlation between gene expression and neuronal connectivity, and Varadan et al (28) identified a genetic rule for chemical synapses through an entropy mini-mization approach.…”
mentioning
confidence: 99%
“…These advances have prompted the development of statistical approaches designed to identify genes involved in neuronal connectivity. At coarser spatial scales, where collections of spatially proximal neurons are profiled together, data availability has led to the development of correlative and predictive approaches that connect regional gene expression and connectivity in the mouse brain (25,26). At the neuronal scale, Kaufman et al (27) demonstrated a correlation between gene expression and neuronal connectivity, and Varadan et al (28) identified a genetic rule for chemical synapses through an entropy mini-mization approach.…”
mentioning
confidence: 99%